Development of an Animal Model Using a Closed System to Study the Sensitivity of a Radiopharmaceutical for the Detection of Gastrointestinal Bleeding - Owunwanne, A.; Mahajan, K. K.; Abdel-Dayem, H. M.; Ericksson, S. B. S.; Sadek, S.; Yacoub, T.; Awdeh, M. (Nuklearmedizin - NuclearMedicine, 1987)
An experimental animal model using a closed system to study the sensitivity of radiopharmaceuticals for the detection and localization of gastrointestinal (Gl) bleeding site in a sheep was developed. This model was validated with 99mTc-DTPA. Radioactivity as low as 85.47 ± 13.32 kBq in a volume of 2.1 ±0.14 ml at a bleeding rate of 0.07 ml/min was detected. Simulated intermittent bleeding experiments indicated that at 1 h after injection of 99mTc-DTPA there was still enough circulating radioactivity to bleed into the gut and that it was possible to perform repeat injection of 99mTc-DTPA as early as 2 h after the first injection.Ein experimentelles Tiermodell (geschlossenes System) wurde entwik-kelt, das die Sensitivität einzelner Radiopharmazeutika in der Entdeckung und Lokalisation gastrointestinaler Blutungen ermöglicht. Dieses Modell wurde am Schaf mit 99mTc-DTPA erprobt. Hiermit konnten Blutungsmengen von 0,07 ml/min (85,47 ± 13,32 kBq/2,1 ± 0,14 ml) entdeckt werden. Die Simulation einer intermittierenden Blutung ergab, daß eine Stunde nach der Injektion von 99mTc-DTPA ausreichende Radioaktivitätsmengen im Blut zirkulieren, um auch dann Blutungen nachzuweisen. Auch die Reinjektion des Tracers nach zwei Stunden erwies sich als brauchbarer Weg.